Peningkatan kemampuan mengenal bangun ruang melalui penggunaan media pop up book pada siswa hambatan intelektual kelas II di SLB Negeri 1 Kabupaten Gowa - St. Kasmawati; Tatiana Meidina; Bastiana Bastiana; Dwiyatmi Sulaminah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
This study aims to determine the effect of using pop-up book media on the ability to recognize spatial shapes in Class II students with intellectual disabilities at SLB Negeri 1 Gowa Regency, South Sulawesi Province, Academic Year 2022/2023. The method used in this research is Single Subject Research (SSR) A-B design. The subjects of this study were students with the initials Rt Z. The study was conducted in 10 sessions in two phases, namely the baseline phase (A 1) of 3 sessions and the intervention phase (B) of 8 sessions. The results of this study indicate that there is an effect of using pop-up book media on the ability to recognize spatial shapes. This is indicated by the value data obtained in the baseline phase (A1) which increases in the baseline phase (B). In addition, based on the data obtained, it was then analyzed using analysis within conditions and analysis between conditions. The results of data analysis within and between conditions showed that the mean level of the Intervention phase (B) increased compared to the baseline phase (A1). Based on this, it can be concluded that there is an effect of using pop-up book media on the ability to recognize spatial shapes in students with mild intellectual disabilities in class I at SLB Negeri 1, Gowa Regency, South Sulawesi Province.